Drinking water salinity and kidney health in southwest coastal Bangladesh: baseline findings of a community-based stepped-wedge randomised trial. (April 2017) - Naser, Abu Mohd; Rahman, Mahbubur; Unicomb, Leanne; Doza, Solaiman; Ahmed, Kazi Matin; Uddin, Mohammad Nasir; Selim, Shahjada; Gribble, Matthew O; Anand, Shuchi; Clasen, Thomas F; Luby, Stephen P
Abstract: Background: Drinking water salinity has contributed to scarcity of potable water in southwest coastal Bangladesh. Drinking saline water has been associated with high blood pressure among communities in southwest coastal Bangladesh, but the effect of water salinity on kidney health is unknown. We aimed to understand the association between drinking water salinity and urinary protein excretion from the baseline findings of a community-based stepped-wedge randomised trial. Methods: We collected 24-h urine from 1185 participants from 532 households and 16 communities in three districts (Khulna, Satkhira, and Bagerhat) of southwest coastal Bangladesh between Nov 17, and Dec 21, 2016, and measured urinary sodium and total protein. We measured electrical conductivity in sampled households' stored drinking water. We estimated water chloride concentration by using a published conversion factor and then estimated daily sodium intake by drinking water assuming sodium ions will be coupled with chloride in water. Among normotensive participants who reported exclusively drinking household stored water, and did not report kidney or heart diseases or diabetes, we determined the effects of daily sodium intake by water and urinary sodium on total protein using hierarchical models accounting for household and community level clustering, and adjusted for age, sex and, weight. Findings: Mean urinary sodium was 164 mmoL/24 h and total protein was 402 mg/24 h. Mean sodium intake through drinking water was 17 mmoL per day. For each 1000 μS/cm higher in drinking water electrical conductivity, there was a 8·2 mmoL/24 h (95% CI 5·3–11·1) higher excretion of 24-h urinary sodium. For each 10 mmoL increase in estimated daily sodium intake through drinking water, there was a 15·9 mg/24 h (95% CI 0·3–31·6) increase in total protein. We estimated a 62·9 mg/24 h (95% CI 29·7–96·1) increase in total protein for each 100 mmoL/24 h increase urinary sodium. We identified 37% participants that had mild proteinuria (total protein: 300–500 mg/24 h) and 20% had moderate or substantial proteinuria (total protein: >500 mg/24 h). Interpretation: Drinking water sodium and urinary sodium were associated with increased protein excretion—a powerful marker for progressive kidney disease—in southwest coastal Bangladesh. Interventions aimed at lowering drinking water salinity could provide benefit to kidney health. Funding: Wellcome Trust, UK.